Profil Buku Antologi Karya Sastra Peserta Didik Paket A Berjudul Pena Kecil Edisi-3 Ditinjau dari Kecerdasan Linguistik - Nasim Hamid; Karsono Karsono (Didaktika Dwija Indria, 2025)
This study aims to describe the linguistic intelligence profile of students at the Ibnu Abbas Klaten Community Learning Center (PKBM) as reflected in the literary anthology “Pena Kecil 03.” This study uses a qualitative approach with content analysis methods. The primary data sources are 17 literary works selected using purposive sampling from a total of 91 works in the anthology. Data collection was conducted through document analysis and interviews. The data were analyzed based on five dimensions of linguistic intelligence, including vocabulary mastery, sentence structure, narrative ability, language creativity, and persuasive ability. The results of the study indicate that the linguistic intelligence profile of the students has distinctive characteristics. The main strengths lie in narrative ability and sentence structure, where the students consistently demonstrate the ability to present stories with complete plots, consistent perspectives, and logical development of ideas. The most dominant characteristic is persuasive ability, which focuses on conveying moral messages both explicitly and implicitly. However, areas for development were identified in the aspect of language variation enrichment, particularly in the use of synonyms and sensory language styles, which are not yet dominant competencies. The conclusion of this study is that the linguistic intelligence profile of PKBM Ibnu Abbas students is characterized by a strong narrative foundation and a strong orientation toward the communication of values, with potential for development in the area of linguistic aesthetics.